Development of anisotropic ferromagnetic composites for low-frequency induction heating technology in medical applications. (March 2021) - Xiang, Z.; Le, M.Q.; Cottinet, P.-J.; Griffiths, P.; Baeza, G.P.; Capsal, J.-F.; Lermusiaux, P.; Della Schiava, N.; Ducharne, B.
Abstract: Modern medical applications such as varicose treatment, hyperthermia, or even endovenous thermal ablation require to bring heat flux locally through the human body. The challenge behind such techniques resides in converting electrical power into heat flux and transfer it directly to the targeted area without contaminating and damaging the surrounding tissues. Low-frequency induction heating (LFIH) of catheters made out of biocompatible magnetic composites is an elegant solution. By inserting the catheter through the varicose to be treated and by exciting it through LFIH, it seems possible to reach a temperature high enough to properly heal the damaged area while preserving the surrounding healthy ones. Although recent published results seem promising, an optimized procedure is still required to achieve further improvements. Many directions lying on the active material formulation have been largely explored in the past (variations of particle content, nature, size, and shape). In this work, we propose an alternative solution, which involves the processing of ferromagnetic composites under a constant homogeneous magnetic field, leading to the strong anisotropic behavior due to particles alignment. Remarkably, experimental results demonstrate that by exciting such anisotropic composites along the alignment direction enhances the LFIH effect by more than 30%. Moreover, improvements can also be noticed in the perpendicular direction, meaning that the structured distribution is enough to increase the ferromagnetic properties. Furthermore, the resulting composite is highly flexible, making it easier to be integrated in several medical devices (e.g. endovenous thermal catheter, electromagnetic tracking system, and so on). Graphical abstract: Image 1 Highlights: Low-frequency induction heating (LFIH) of a ferromagnetic catheter is used for a varicose treatment. Anisotropic ferromagnetic catheter exhibits improved LFIH answer. A anisotropic ferromagnetic catheter is obtained by curing under magnetic excitation. Particle alignments are observed in the anisotropic ferromagnetic catheter.